2007
DOI: 10.1002/mar.20181
|View full text |Cite
|
Sign up to set email alerts
|

Guilt appeals: Persuasion knowledge and charitable giving

Abstract: This paper applies the persuasion knowledge model to explain consumers' responses to charity guilt appeals. With data obtained through a stimuli-driven survey, the research examines the relationships between knowledge of persuasion tactics and charities, and the level of felt guilt experienced in response to an advertisement and subsequent donation intentions. The findings show that guilt arousal is positively related to donation intention, and that persuasion and agent knowledge impact the extent of guilt aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
247
0
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(269 citation statements)
references
References 62 publications
15
247
0
7
Order By: Relevance
“…. For instance, research on charitable fundraising has demonstrated that inducing guilt through vivid portrayals of others' suffering, which elicits "other-oriented empathy" (Tangney, Stuewig, & Mashek 2007), can effectively increase donation intentions (Hibbert, Smith, Davies, & Ireland 2007).…”
Section: Other-oriented Outcomes Versus Self-oriented Distressmentioning
confidence: 99%
“…. For instance, research on charitable fundraising has demonstrated that inducing guilt through vivid portrayals of others' suffering, which elicits "other-oriented empathy" (Tangney, Stuewig, & Mashek 2007), can effectively increase donation intentions (Hibbert, Smith, Davies, & Ireland 2007).…”
Section: Other-oriented Outcomes Versus Self-oriented Distressmentioning
confidence: 99%
“…Their research addresses the impact of guilt on donations but does not address the antecedents of guilt. Additionally, research by Hibbert, Smith, and Ireland (2007) demonstrates a relationship between guilt and donation intention, which is impacted by persuasion and agent knowledge. These studies provide a useful starting point for further assessing the process through which guilt impacts donation intention.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, in a study by Haynes et al (2004), participants who read a negative appeal felt that the advertiser was manipulating them more than participants reading a positive appeal but still reported higher donation and volunteering intentions (see also Lord, 1994). Also, research by Hibbert, Smith, Davies, and Ireland (2007) found that perceived manipulative intent and the intention to donate in fact correlated positively with each other, indicating that attitudes and behavior do not always go hand in hand.…”
mentioning
confidence: 99%